PRAKTEK MANAJEMEN LABA DI INDONESIA: KOMITE AUDIT, KOMISARIS INDEPENDEN, ARUS KAS OPERASI - Intan Permata Sari; Timothy Tjandra; Amrie Firmansyah; Estralita Trisnawati (Ultimaccounting Jurnal Ilmu Akuntansi, 2021)
Abstract— The purpose of this study is to examine the effect of independent variables, namely independent commissioners, operating cash flows, and audit committees, on earnings management. The data for this research is sourced from the financial statements of manufacturing companies that focus on the consumer goods industry listed on the Indonesia Stock Exchange from 2015 to 2019. Sampling was carried out by purposive sampling totaling 104 observations sourced from www.idx.co.id. This study's test is panel data regression analysis with a fixed-effect model. This study indicates that the independent commissioner is positively associated with earnings management, while the audit committee and operating cash flow are not associated with earnings management. The Indonesian Financial Services Authority needs to improve the rules for implementing corporate governance and monitoring the implementation of the corporate governance structure, and coordinating with the Indonesian Institute of Accountants to improve disclosure of information in financial statements. Keywords:, Audit Committee; Earnings Quality; Independent Commissioner; Operating Cash Flow